The impact of digitalization on the labor market and social security of employees - Šarotar Žižek, Simona; Mulej, Matjaž (Anali PAZU HD, 2022)
Research also shows that in workplaces all the more increase the both the time pressures as well as the scope of work. New technologies lead to growing demands for permanent availability. The foregoing leads to the overgrowth of psychosocial risk factors in the work environment. People, therefore, working under the constant pressure of short deadlines, the complexity of complex tasks and unpredictable situations. All of this is reflected then in their health status. It is basically for this that the use of technology in the workplace may be more than undermine productivity - can reduce the physical and mental well-being of employees because a bad impact on sleep, causing anxiety and depression, etc, though the use of digital technology from the viewpoint of ergonomics and provides the safety and health at the workplace a lot of advantages.
Keywords: digitization; labour market; social security; employees; social responsibility